The Context of Education on Teaching English between Indonesia and Singapore: A Review of Basic Elements - Kurniawan Kurniawan; Rusdinal Rusdinal; Azwar Ananda; Nurhizrah Gistituati (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
This review paper aims at giving a short outline regarding the examination of Teaching English Language instructing and teaching English Language as a Foreign Language (TEFL) between Indonesia and Singapore. The review based its analysis on a few elements which affect instructing and learning TEFL in the Indonesian context and Singapore, i.e., educator capabilities, teaching English language capability, homeroom size, understudies' inspiration, study hall situated learning, and restricted wellsprings of learning. The review highlighted that these are the factors which give impact on instructing and learning achievement. The review conducted its analysis under few limitations at work between language strategy and language encouraging study hall rehearsed in the two nations. This paper points out that understudies have different inspirations and foundation qualities altogether, making it hard to plan as an asset to a solitary educational program which will suit all (or at least most) understudies of the nation. Moreover, financial support for educators, resourcing, and the probability of huge class capacity in the Indonesian context appear differently in relation to Singapore. Low instructor compensations in Indonesia cause most educators to work in extra positions that lessen the time they can allot for exercise arrangement, endeavors to create practices and undertaking advancement by upgrading expert information, whereas instructors in Singapore are doing the full education time. Finally, the strategy and educational plan legislative issues have a significant impact on TEFL examination, thus understanding and correctly implementing them needs to be a requirement to language learning.